Variable Ratio of Hepatitis C Virus RNA to Viral Core Antigen in Patient Sera - Schüttler, Christian G. (American Society for Microbiology, 2004)
Quantification of hepatitis C virus (HCV) core antigen and RNA in serum samples leads to a highly variable ratio of both. It is not clear whether this is due to the inaccuracy of RNA quantification or whether both are independent parameters in a certain range. We established a real-time reverse transcription (RT)-PCR for HCV RNA that combines very high sensitivity with a large dynamic range and minimal standard deviations. The assay was calibrated with the first international standard, 96/790, and the international genotype panel for HCV from the National Institute of Biological Standardisation and Control. A linear readout was obtained between 200 and 5 × 10(7) IU/ml. The detection limit was 80 IU/ml, the reproducibility was <0.05 log, and the standard error within one run was <0.01. Comparison of the method with the Roche Monitor competitive RT-PCR revealed its high accuracy. The core protein concentration was determined within a range from 1.5 to 400 pg/ml by using the preliminary trak-C assay from Ortho Clinical Diagnostics. Correlating the HCV RNA levels with core antigen concentrations in 197 serum samples from 23 interferon-treated patients, a average ratio of 7,900 IU of HCV RNA per pg of core antigen was estimated, but the variability of this ratio exceeded largely the variability of the two assays, ranging from 50 to 20,000 IU/pg. Theoretically, HCV should contain ca. 43,000 IU of RNA/pg core. In conclusion, the core antigen assay seems to detect, in addition to complete virions, RNA-free core protein structures, which enhances its sensitivity (98% in this group). The variable ratio of RNA and core protein is not mainly due to standard deviations of quantification but could be an additional parameter for treatment follow-up and state of viral replication.